2018
DOI: 10.1175/jcli-d-17-0884.1
|View full text |Cite
|
Sign up to set email alerts
|

The Internal Generation of the Atlantic Ocean Interdecadal Variability

Abstract: Numerical simulations of a realistic ocean general circulation model forced by prescribed surface fluxes are used to study the origin and structure of intrinsic interdecadal variability of the ocean circulation. When eddy-induced turbulent diffusivities are low enough, spontaneous oscillations of the Atlantic meridional overturning circulation (AMOC) with periods O(20) yr and amplitude O(1) Sv (1 Sv ≡ 106 m3 s−1) emerge. The transition from the steady to the oscillatory regime is shown to be consistent with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(64 citation statements)
references
References 85 publications
9
55
0
Order By: Relevance
“…More specifically, the variability disappears for diffusivity values that are typically in the range of observational estimates (500 − 1000 m 2 s −1 ) casting therefore some doubts on the relevance of this self-sustained internal mode for the observed variability. The same conclusions are found for the influence of the isopycnal diffusivity within the Gent and Mcwilliams (1990) parameterization in a realistic configuration (Arzel et al 2018). Moreover, (LaCasce and Pedlosky 2004) have shown that large-scale anomalies associated with Rossby waves are prone to meso-scale baroclinic instability; they further suggested that the presence of Rossby waves in the mid to high latitudes is unlikely because at these latitudes, Rossby wave periods are slow compared to the destabilization 5 Accepted for publication in Journal of Climate.…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…More specifically, the variability disappears for diffusivity values that are typically in the range of observational estimates (500 − 1000 m 2 s −1 ) casting therefore some doubts on the relevance of this self-sustained internal mode for the observed variability. The same conclusions are found for the influence of the isopycnal diffusivity within the Gent and Mcwilliams (1990) parameterization in a realistic configuration (Arzel et al 2018). Moreover, (LaCasce and Pedlosky 2004) have shown that large-scale anomalies associated with Rossby waves are prone to meso-scale baroclinic instability; they further suggested that the presence of Rossby waves in the mid to high latitudes is unlikely because at these latitudes, Rossby wave periods are slow compared to the destabilization 5 Accepted for publication in Journal of Climate.…”
Section: Introductionsupporting
confidence: 80%
“…The same mode of variability was later demonstrated to exist in a realistic configuration of the North Atlantic (Sévellec and Fedorov 2013). Arzel et al (2018) further showed that the internal ocean mode produces maximum SST variance in the western part of the subpolar gyre, in agreement with the observed signature of the AMO in the North Atlantic.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…The processes responsible for the AMOC decadal climate variability were reported to be due to (1) the atmospheric stochastic forcing (Frankignoul & Hasselmann, ; Delworth & Greatbatch, ), (2) self‐sustained oceanic intrinsic variability (Arzel et al, ; Sérazin et al, ), or (3) coupled mode of variability (Timmermann et al, ). Most low‐resolution ocean models show little variability when using bulk formulation as surface boundary condition (Danabasoglu et al, ).…”
Section: Introductionmentioning
confidence: 99%